Punitiveness Beyond Criminal Justice: Punishable and Punitive Subjects in an Era of Prevention, Anti-Migration and Austerity - Carvalho, Henrique (The British journal of criminology, 2020)
This article advances a holistic conceptualization of punitiveness that acknowledges its complexity and contemporary social and political pervasiveness. We argue that punitiveness is best understood as a phenomenological complex operating at a personal, symbolic, political and structural level, which borrows from, but extrapolates the confines of criminal justice institutions. The article examines limitations in articulations of punitiveness in criminological scholarship, and then draws on three contemporary case studies to investigate how the political deployment of anxieties and hostilities around the ‘crises' of prevention, anti-migration and austerity reveal and reproduce punitive logics. It then outlines an original conceptual framework to argue that punitiveness ultimately revolves around the construction of, and dynamics between, punitive and punishable subjects.